Islamic counseling guidance in improving the religiusity Of high school students - Iskandar, Dadang Hamdan; Nusantari, Widhya; Alkattani, Abdul Hayyie (Tawazun: Jurnal Pendidikan Islam, 2022)
The presence of Islamic guidance and counceling administrations in schools can be utilized as a technique by instructors in giving direction and inspiration to understudies as per the lessons of the Qur'an and Hadith by applying strict qualities as an aide or establishment for understudies in conquering every one of the issues they face. Absence of strict arrangement is one of the variables that causes freak conduct in young people, this can happen when people don't have a solid strict establishment so they are effectively affected by natural circumstances, so there should be a course of coaching endlessly learning strict training. Guidance and counseling in the perspective on Islam is a work made to take care of an issue that happens in an individual in view of Islamic standards. In light of the capacity of Counseling Guidance in the perspective on Islam, everything is done to improve the capability of understudies and make an honest effort to figure out the thing they are going through to acquire the right arrangement and have a proper life. God's blessings both in this world and in the last yaumil. Abstrak Kehadiran program bimbingan dan konseling Islam di sekolah dapat dimanfaatkan sebagai media bagi pengajar dalam memberikan arahan dan inspirasi kepada siswa sesuai pelajaran Al-Qur'an dan Hadits dengan menerapkan sifat-sifat yang tegas sebagai pembantu atau pedoman bagi siswa dalam menyelesaikan setiap permasalahan yang mereka hadapi. Tidak adanya pengaturan yang tegas merupakan salah satu variabel yang menyebabkan terjadinya perilaku aneh pada remaja, hal ini dapat terjadi apabila masyarakat tidak memiliki pendirian yang tegas dan kokoh sehingga secara efektif dipengaruhi oleh keadaan sosial. Oleh karenanya perlu adanya suatu program pembinaan tanpa henti dengan pengawasan yang ketat. Bimbingan dan Konseling dalam Perspektif Islam adalah suatu usaha yang dilakukan untuk menangani suatu persoalan yang terjadi pada diri individu menurut standar Islam. Mengingat kapasitas Bimbingan Konseling dalam perspektif Islam, segala sesuatu dilakukan untuk meningkatkan kemampuan siswa dan berusaha secara jujur untuk mengetahui apa yang mereka alami untuk mendapatkan pengaturan yang benar dan memiliki kehidupan yang layak. Sehingga mendapatkan keberkahan dari Allah baik di dunia maupun dihari akhir nanti.